Gambaran Pola Konsumsi Zat Gizi Makro dan Tekanan Darah Pada Lansia di Desa Sibanggede, Kecamatan Abiansemal, Kabupaten Badung - Ni Nyoman Kirana Putri; Pande Putu Sri Sugiani; Lely Cintari (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
Elderly susceptible to diseases associated with aging process one of them hypertension. This study aims to determine the pattern picture of macro nutrient consumption and blood pressure in elderly in Sibanggede Village. The type of this study was observational with Cross Sectional design. Based on the results of research on 79 samples, amounted to 58.46% the amount of energy consumption has more abnormal blood pressure. 70.76% of the total protein consumption has more abnormal blood pressure. 72.30% of total fat consumption has abnormal blood pressure. And as much as 67.69% the total consumption of carbohydrates more have abnormal blood pressure. A total of 78.57% different types of foodstuffs in both categories have normal blood pressure and equal to 84.61% different types of food in the category of either have abnormal blood pressure. Approximately 35.71% of the recommended feeding frequency had normal blood pressure and 72.30% of the recommended feeding frequency had abnormal blood pressure. In relation to the largest proportion is the sample with abnormal blood pressure levels with macro nutrient category consumption more than the amount of energy consumption, protein, fat and carbohydrate. Therefore it should be given counseling about setting the right consumption pattern to keep blood pressure to stay normal.Keywords: consumption pattern, blood pressure, elderly